1987
DOI: 10.3382/ps.0660280
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pantethine Supplementation to Diets with Different Energy Cereals on Hepatic Lipogenesis of Laying Hens

Abstract: Effects on dietary pantethine supplementation on hepatic lipid accumulation and on the activities of lipogenic-related enzymes in the liver were studied in Single Comb White Leghorn laying hens fed isocaloric and isonitrogenous diets containing corn or barley as the carbohydrate source. Addition of 200 ppm pantethine to the corn-soy (CS) basal diet significantly reduced abdominal fat weight, liver triglyceride, as well as total cholesterol and 17 beta-estradiol concentrations in the plasma. Activities of citra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Many studies have demonstrated that pantethine has anticatabolic properties in fatty acid synthesis and stimulates fatty acid oxidation [ 82 , 83 ]. Pantetheine has been used in humans as a lipid-lowering drug and dietary pantethine has also been shown to improve liver lipogenesis in laying hens [ 84 , 85 ]. In our study, the decreased level of pantethine in the cecum of the late-phase laying hens fed an LL diet was also significantly correlated with the downregulated expression of genes related to fatty acid beta-oxidation and enriched key cecal bacteria (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated that pantethine has anticatabolic properties in fatty acid synthesis and stimulates fatty acid oxidation [ 82 , 83 ]. Pantetheine has been used in humans as a lipid-lowering drug and dietary pantethine has also been shown to improve liver lipogenesis in laying hens [ 84 , 85 ]. In our study, the decreased level of pantethine in the cecum of the late-phase laying hens fed an LL diet was also significantly correlated with the downregulated expression of genes related to fatty acid beta-oxidation and enriched key cecal bacteria (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the reduced plasma TG and TCH further indicated that the capacity of endogenous lipid transport out of the liver in fish fed with high-fat diets is 10 Aquaculture Nutrition weakened, resulting in liver fat deposition. Recently, many studies have suggested that PA supplementation and its derivatives can reduce plasma TG and TCH, but the effect showed a dose specificity which is manifested as excess PA supplementation inhibiting the lipid elimination [38][39][40].…”
Section: Discussionmentioning
confidence: 99%